Pengaruh Dana Pihak Ketiga, BOPO, ROA Dan NPL Terhadap Penyaluran Kredit Pada Perbankan Indonesia Yang Listing Di Bursa Efek Indonesia Periode 2017-2021 - Yuwanto Yuwanto; Febri Wibowo Simatupang; Anggel Valentina Wijaya; Ferdinand Napitupul; Hantono Hantono (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to determine the effect of third party funds, BOPO, ROA and NPL on credit distribution in Indonesian banking listed on the Indonesia Stock Exchange in period 2017-2021. This research is a quantitative research. The population in this study is all banks listed on the IDX, totaling 47 companies during 2017-2021. The research sample used purposive sampling method, so the number of samples was 24 companies. The statistical method used is multiple linear regression analysis. The results showed that partially stated Third Party Funds had an effect on Credit Distribution, while BOPO, ROA and NPL had no effect on Credit Distribution. And also simultaneously states Third Party Funds, BOPO, ROA and NPL have an effect on Credit Distribution. The conclusion of this study is that only Third Party Funds, BOPO, ROA and NPL affect Lending in Indonesian Banking Listings on the Indonesia Stock Exchange in the period of 2017-2021. Keywords: Third Party Funds, BOPO, ROA, NPL and Lending